APOTROPAIOS: PROTEÇÃO CONTRA A MALDIÇÃO - Cândido, Maria Regina (PHOÎNIX, 2020)
Amulets were in demand for every imaginable situation in life. The use of magic for protection and deliverance from diseases must have been widespread from the earliest times. A phylactery — comes from the Greek verb OuAducrEtvi to protect — is a type of amulet used more specifically to protect an individual or community from some impending calamity or plague.